Two Sudden and Unexpected Deaths of Patients with Schizophrenia Associated with Intramuscular Injections of Antipsychotics and Practice Guidelines to Limit the Use of High Doses of Intramuscular Antipsychotics - Nasratullah Wahidi; Katie M. Johnson; Allen Brenzel; Jose de Leon (Case Reports in Psychiatry)
Intravenous haloperidol has been associated with torsades de pointes (TdP). These two sudden deaths were probable adverse drug reactions (ADRs) following intramuscular (IM) antipsychotics. The autopsies described lack of heart pathology and were highly compatible with the possibility of TdP in the absence of risk factors other than the accumulation of antipsychotics with a high serum peak after the last injection, leading to death within hours. The first case was a 27-year-old African-American male with schizophrenia but no medical issues. His death was probably caused by repeated IM haloperidol injections of 10 mg (totaling 35 mg in 2 days). The second case involves a 42-year-old African-American female with metabolic syndrome. Her probable cause of death was the last ziprasidone IM injection of 20 mg in addition to (1) three extra haloperidol doses (2 hours before the ziprasidone injection, 5 mg oral haloperidol; approximately 21 hours earlier, 5 mg oral haloperidol; and 2 days prior, one 10 mg IM haloperidol injection), (2) 10 mg/day of scheduled oral haloperidol for 6 days before death, and (3) a long-acting paliperidone injection of 156 mg 18 days before death. The study of haloperidol glucuronidation and its impairment in some African-Americans is urgently recommended.